1α,25-Dihydroxyvitamin D3 Supplementation during Pregnancy Is Associated with Allergic Rhinitis in the Offspring by Modulating Immunity - Liqing Zhang; Haifeng Ni; Zhen Zhou; Xiaoyang Yuan; Junbo Xia; Bo Jiang; Yong Li (Journal of Immunology Research)
Background. Maternal supplementation with 1α,25-dihydroxyvitamin D3 (VD3) has immunologic effects on the developing fetus through multiple pathways. This study was aimed at investigating the effects of VD3 supplementation on immune dysregulation in the offspring during allergic rhinitis. Methods. Different doses of VD3 as well as control were given to pregnant female mice. Ovalbumin (OVA) challenge and aluminum hydroxide gel in sterile saline were used to induce allergic rhinitis in offspring mice. Nasal lavage fluids (NLF) were collected, and eosinophils were counted in NLF 24 hours after the OVA challenge. Th1, Th2, Th17, and Treg subtype-relevant cytokines, including IFN-γ, IL-4, IL-10, IL-17, TGF-β, and OVA-IgE levels from the blood and NLF of offspring mice, were detected by the enzyme-linked immunosorbent assay (ELISA) method. The Treg subtype was analyzed by flow cytometry. Treg cells were purified from offspring and were adoptively transferred to OVA-sensitized allogenic offspring mice. The outcomes were assessed in allogenic offspring. Results. Our data showed that VD3 supplementation significantly decreased the number of eosinophils, basophils, and lymphocytes in the peripheral blood and NLF. The proportion of CD4+CD25+FoxP3+Tregs had a positive correlation with VD3 in a dose-dependent manner. The levels of serum IgE, IL-4, and IL-17 were decreased while the expressions of IFN-γ, IL-10, and TGF-β were significantly enhanced in VD3 supplementation groups. Adoptive transfer CD4+CD25+FoxP3+Tregs of VD3 supplementation groups promoted Th1 and suppressed Th2 responses in the offspring during allergic rhinitis. Conclusion. Our findings indicated that low dose VD3 supply in pregnant mice’s diet suppressed Th2 and Th17 responses in allergic rhinitis by elevating the Th1 subtype and the proportion of CD4+CD25+FoxP3+Tregs in offspring. It suggested that low dose VD3 supply may have the potential to act as a new therapeutic strategy for allergic rhinitis.